2013
DOI: 10.1007/s00380-013-0424-0
|View full text |Cite
|
Sign up to set email alerts
|

Electroanatomically estimated length of slow pathway in atrioventricular nodal reentrant tachycardia

Abstract: The length of the slow pathway (SP-L) in atrioventricular (AV) nodal reentrant tachycardia (NRT) has never been measured clinically. We studied the relationship among (a) SP-L, i.e., the distance between the most proximal His bundle (H) recording and the most posterior site of radiofrequency (RF) delivery associated with a junctional rhythm, (b) the length of Koch’s triangle (Koch-L), (c) the conduction time over the slow pathway (SP-T), measured by the AH interval during AVNRT at baseline, and (d) the distanc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
13
0

Year Published

2016
2016
2020
2020

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 17 publications
(16 citation statements)
references
References 36 publications
3
13
0
Order By: Relevance
“…Bhaskaran et al applied RF with a power of 40 to 50 W and a maximum temperature of 70℃ using a nonirrigated catheter whereas the RF power was 15 to 30 W in our study. An investigation conducted with similar RF power to ours reported that the distance from His to successful ablation was 11.6 ± 4.7 mm, which was almost the same result as ours …”
Section: Discussionsupporting
confidence: 87%
See 1 more Smart Citation
“…Bhaskaran et al applied RF with a power of 40 to 50 W and a maximum temperature of 70℃ using a nonirrigated catheter whereas the RF power was 15 to 30 W in our study. An investigation conducted with similar RF power to ours reported that the distance from His to successful ablation was 11.6 ± 4.7 mm, which was almost the same result as ours …”
Section: Discussionsupporting
confidence: 87%
“…Following the development of the 3D mapping system, many kinds of arrhythmic disease became easier to ablate. Although previous studies on AVNRT with and without the 3D mapping system showed the distance from the His potential to the successful ablation point, information concerning the borderline between areas of appropriate JR and excessively fast JR was not available. If the borderline could be clarified and marked on the 3D mapping system, a more precise point for the successful ablation of AVNRT could be identified, and the ablation procedure could be conducted with improved safety and success.…”
Section: Introductionmentioning
confidence: 99%
“…Previous studies suggested that the slow-fast AVNRT patients with longer A-H interval over the antegrade slow pathway conduction had greater distance between the successful ablation site for antegrade slow pathway and His potential recording site. 16 Furthermore, it is also suggested that the longer conduction time over slow pathway needed to transverse a longer anatomical distance. 17,18 We also previously reported that the patients with 2:1 AV conduction block during AVNRT tachycardia had shorter TCL and A-H interval during tachycardia.…”
Section: The Ld-atp Sensitivity and The Proximity To His Recording Armentioning
confidence: 99%
“…Finally, the reader suggested analysis of the AH interval during AVNRT based on age, as other data in the literature have suggested that the AH interval could be associated with the physical length of the slow pathway . Others have also suggested that the length of the slow pathway is critical to the development of AVNRT, as perhaps there is a critical “length” required for the development of tachycardia, and this length factor may explain why AVNRT is rarer in young children .…”
Section: Intervals With Relation To Agementioning
confidence: 99%